PERCEPTIONS OF THE UNIVERSE: THE PARADIGM SHIFT - Rimbo Gunawan (Sosiohumaniora, 2004)
This essay explores the development of people perception about the universe. There have been paradigms shift regarding time, space, and matter over the entire universe. What have the paradigms been? What is knowledge, how it relates to the reality and its implication to the human being in general and to the social sciences in particular? Keywords: Universe, time, space, matter, paradigm, social sciences